FACTORS INFLUENCING TAX EVASION AMONG TAXPAYERS IN UZBEKISTAN: AN EMPIRICAL ANALYSIS - Zafar Akhmedov (Modern American Journals, 2026)
Tax evasion remains a significant challenge to fiscal sustainability and socio-economic development in transition economies, including Uzbekistan. Despite extensive tax reforms aimed at reducing informality and strengthening compliance, tax evasion persists at high levels. This study aims to empirically examine the key behavioral, institutional, and regulatory factors influencing tax evasion among taxpayers in Uzbekistan.
Keywords: Tax evasion; Tax compliance; Tax morale; Tax fairness; Institutional trust; Tax complexity; Uzbekistan; Shadow economy.